A discursividade literária em João Anzanello Carrascoza: por uma episteme do ensino de literatura - França, Thyago Madeira (2018)
This study has as its main goal the construction of an episteme for the teaching of literature, based on the aesthetics discursiveness of the work Espinhos e Alfinetes (Thorns and Pins) by João Anzanello Carrascoza. We advocate a discursive and transgressive teaching of literature, since we conceive the literary work as a discursive event and not as a mere object of description and aesthetic fruition. Therefore, we propose to rethink the teaching of literature in the theoretical perspective of critical, discursive, transgressive and undisciplined Applied Linguistic organized by Moita Lopes (2006;2013), in interface with Michel Pêcheux’s studies (1997;2006;2010) and with the Bakhtin Circle’s dialogic-polyphonic philosophy (2006;2011;2012;2017). This theoretical -philosophical positioning allowed the construction of a different prospective about the teaching of literature in schools, as well as the episteme functioning for this teaching. Carrascoza’s tales were studied in the beat between the artistic manifestation and the discursiveness, both configured within the event of the literature work, from which emerged enunciative regularities that, by recurrence or singularity, produced meaning effects in the interior of the event. These regularities gave rise to processes of discursive memory constitutive of the discursiveness that interpellated the episodes of death in the tales, once the instauration of these processes of death discursive memory was determinant for the analysis of the meaning effects and the subject-instances that gravitated around the event of the literature work. For the development of the analysis, the narratives were scanned from methodological devices of discursive analysis (matrices, axioms and N-essence), which allowed the mapping of regularities within the literature work as a whole, the construction of operator-utterances that delineated the constitutive discursiveness of the discursive conjuncture, as well as the association of concepts that emerged from the combination among the constituent, constituted and constitutive elements of the event. Such analytical devices which were used for the scanning of the discursive event of the literature work were not only the methodological foundation for the discursive analysis of Carrascoza’s tales, but also the basis for the teaching of literature episteme proposed in this thesis.